Chapter On the Notion of Analyticity in Proof Theory - Indrzejczak, Andrzej (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Several notions of analytic proof are considered in the paper. After brief recollection of historically important approaches to this notion we focus on contemporary applications of this term. In particular, the relationships between cut elimination, subformula property and analyticity of proof in sequent calculus are examined.